ANTIOXIDANT ACTIVITY AND CARDIOPROTECTIVE ACTIVITY OF BANGUN-BANGUN LEAVES (PLECTRANTHUS AMBOINICUS LOUR.) ETHANOLIC EXTRACT - Tarigan, Modesta Harmoni; Harahap, Urip; Dalimunthe, Aminah; Nerdy, Nerdy (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objectives: The objectives of this study were to determine the antioxidant activity and cardioprotective activity of bangun-bangun leaves ethanolic extract. Methods: Bangun-bangun leaves ethanolic extract was obtained by maceration process. The antioxidant activity test was performed by 2,2'-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid) free radical scavenging method with various concentrations of extract. The absorbance was measured by visible spectrophotometric method and calculated the inhibitory concentration (IC50) value for antioxidant activity analysis. Cardioprotective activity test was performed by measuring the cardiac troponin T (cTnT) level, creatine kinase-muscle/brain (CK-MB) level, and histology of the heart tissue. Animals induced with doxorubicin at the 8th day and the 9th day, bangun-bangun leaves ethanolic extract was administered from the 1st day to the 9th day with various doses of extract. Results: Bangun-bangun leaves ethanolic extract had IC50 value of 57.79 Î¼g/mL. Difference dose of bangun-bangun leaves ethanolic extract shows difference cardioprotective activity. Bangun-bangun leaves ethanolic extract at dose 300 mg/kg bw did not differ significantly to the positive control group and normal group. The higher the dose of an extract the greater the decrease in cTnT and CK-MB levels and increase protection against heart damage. Conclusion: Bangun-bangun leaves ethanolic extract had strong antioxidant and had cardioprotective activity. Â 